Snapshots : good learning and teaching in physics in Australian universities : a resource booklet from the project Learning Outcomes and Curriculum Development in Physics. (Monash University. School of Physics, 2005)
Describes creative ways of engaging students in effective learning, drawn from physics departments across Australia.